Factores estresantes y grado de satisfacción laboral del profesional de enfermería Hospital Belén de Trujillo - Suárez Torres, Sheila Roxana (2017)
The present research study, descriptive, correlational, cross-section, carried out with the aim of determining the relationship between environmental, labor, personal factors and degree of job satisfaction the emergency services and intensive care unit nursing professionalof the Hospital Belen of Trujillo. The sample population consisted of 30 nurse that met the inclusion criteria. For the obtaining of data was used a format survey of job satisfaction and a test to determine the stress factors. For the statistical analysis Chi-square test was used, it was considered (P < 0.05). The results were presented in statistical tables of one and double entry, of numerical and percentage form. Conclusion: the 73.3% of nurses presented a medium presence of environmental stressors, 70% obtained minimum presence of occupational stressors, and 90% of participants had minimum presence of personal stress factors. In addition the highest percentage (76.7%) showed a medium degree of job satisfaction and a 23.3% obtained a high degree of job satisfaction. There is no significant dependence (p>0.05) between stressors: environmental, labor, personnel and the degree of job satisfaction.